Mild cutaneous reactions to drugs - Crisafulli, Giuseppe; Franceschini, Fabrizio; Caimmi, Silvia; Bottau, Paolo; Liotti, Lucia; Saretta, Francesca; Bernardini, Roberto; Cardinale, Fabio; Mori, Francesca; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Adverse reactions to drugs are not frequent in childhood. Cutaneous reactions are the most frequent in this age group. Mild cutaneous reactions are immediate or delayed adverse reactions that do not seriously compromise the clinical condition of children. The patients usually early improve and recover the state of health. Although it is difficult to define the prevalence accurately, we could affirm that the rate adverse reaction to drugs are often over estimated by both the families and the physicians. Therefore, children may be prone to loss of school days and inappropriate or sub-optimal treatments. However, the identification of a true adverse reaction to drugs allows adequate treatment and alert to further exposure to harmful drugs.